Towards Adoption of Standards for Communication Infrastructure/Technologies in Healthcare Systems in LMICs: Theories, Practice and Evaluation - Egwar, Andrew Alunyu; Ssekibuule, Richard; Nabukenya, Josephine (In HEALTHINF, 2020)
While electronic health offers great promise to improve healthcare in low and middle-income countries (LMICs), the communication infrastructure/technologies (CI/T) requires standards to improve the current state of none to limited interoperability. This study reviewed theories that inform the assessment of the health system’s readiness to adopt ehealth CI/T standards. The study involved a scoping review of published articles reporting adoption to the use of ICT, technologies, and standards in health. Articles published in English between 2012-2019 were identified through PubMed Central and Google Scholar. Also, grey literature from websites of WHO, standards development organisations and Uganda’s Ministry of Health were searched. Data extraction involved coding to identify key themes that inform the readiness of health systems to adopt standards for eHealth CI. Of the 3,817 published articles, only 32 met the inclusion criteria. 17 grey literature was also included in our discussion. Results identified determinants for eHealth CI/T and that concepts from the technology adoption theories can be used as metrics to assess readiness to adopt standards for ehealth CI/T. The metrics for drivers to adopt standards were higher than inhibitors in Uganda’s health system. The metrics will lead to the development of a readiness assessment framework.
Keywords: Adoption, Communication Infrastructure, Health Information Exchange, Ehealth, Readiness, Standards